Management Analysis of The Implementation of The Utmost Good Faith Principle In Insurance Agreements - Hanna Yulita; Erlina Puspitaloka Mahadewi (International Journal of Health and Pharmaceutical (IJHP), 2025)
This study analyzes insurance with an agreement between two parties, namely an insurance company called the insurer and a policyholder called the customer, where the insurance company promises to provide financial protection against risks such as accidents, illness, death and others while the customer makes premium payments periodically or all at once. One of the important principles in making an insurance agreement is Utmost Good Faith (Good Faith). In Indonesia, there are several examples of cases of violations of the principle of utmost good faith such as not disclosing previous illnesses, misuse of Health Insurance benefits, not providing clear information regarding the risks and benefits of insurance such as unit links. Therefore, insurance companies are challenged to be able to obtain honest information from customers and must convince customers, to provide information and claim reimbursement in accordance with the agreement made in the policy, both methodically and materially. This study uses a qualitative method. The source used is Google Scholar using search keywords are the principle of utmost good faith and insurance agreement. Research results: this study wants to know the implementation of the principle of utmost good faith in Insurance, problems, how to overcome and solutions in the future to benefit the Insurance business in Indonesia.